Public Perception of Food Poisoning Reports within the Free Nutritious Meal (MBG) Program - Ludina, Deva Anggreani; Rohid, Nibrosu; Surya, Andi (Jurnal Komunikasi Profesional, 2025)
This study aims to analyze public perception regarding media coverage of food poisoning cases within the "Free Nutritious Meal" program and its impact on risk perception, trust levels, and public acceptance. Food poisoning issues widely reported across mass media and social media platforms have the potential to shape public views on food safety and the quality of program management. Adopting a quantitative approach with an explanative survey method, data were collected through questionnaires distributed to respondents exposed to related news coverage. Data analysis utilized descriptive statistics and linear regression to examine the relationships between news exposure, risk perception, public trust, and program acceptance. The results indicate that the intensity of news exposure significantly influences the formation of risk perception. Frequent access to information regarding poisoning cases leads to higher levels of concern regarding food safety. Increased risk perception is correlated with a decline in public trust, particularly when media reports emphasize negligence. However, individuals with high pre-existing trust in the government tend to remain supportive of the program, viewing the nutritional benefits as outweighing the reported risks. The findings also reveal that emotional factors and health issues involving children amplify risk perceptions. The media plays a vital role in constructing social reality and influencing the program's image. This study concludes that negative reporting affects not only safety perceptions but also policy legitimacy. Consequently, transparent, responsive, and evidence-based risk communication strategies are essential to maintain public trust and ensure the sustainability of the Free Nutritious Meal program.